Pengembangan Pemikiran Tentang Biaya Tambahan Restrukturisasi terhadap NPF (Non Performing Financing) Pembiayaan Murabahah - Fadhil, Fakhry; Mukhlas, Oyo Sunaryo; Hakim, Atang Abdul (Program Studi Hukum Ekonomi Syariah (Muamalah), 2025)
Rescheduling in murabahah financing in Islamic banking as well as the legal basis for the enactment of additional fees based on the DSN-MUI fatwa. Rescheduling is one of the restructuring instruments that aims to provide leeway for customers who have difficulty paying obligations. However, it is different from the provisions of POJK No.11/POJK.03/2015 that there are no additional fees. The results of the research that the basis of this DSN fatwa can be traced through the ʿillat of the law of fiqh muamalah. First, the rule of al-ghurm bil-ghunm emphasizes that every profit must be in line with the risk or cost, so it is natural that the customer who wants to change the contract also bears the costs incurred. Second, the rule of al-masyaqqah tajlibut-taysir shows that difficulties bring convenience, where rescheduling is a form of relief so that customers avoid default, but the convenience still requires compensation for the administrative and legal consequences that arise. Third, it emphasizes the difference between riba and ujrah, where additional costs are interpreted as transparent real cost recovery, not speculative additions. Fourth, from the perspective of maqāṣid al-sharīʿah, this ability reflects the principles of justice (al-ʿadālah) and benefit (al-maṣlaḥah), so that there is no unilateral loss for the bank or the customer.